FORMULASI KEDAULATAN RAKYAT ATAS ANGGARAN NEGARA DALAM UUD 1945 PASCA AMANDEMEN - Paputungan, Merdiansa (Mimbar Hukum, 2024)
Abstract This research stems from various criticisms of the results of the amendment to Article 23 of the 1945 Constitution, which basically views that the results of the amendment have degraded the philosophy of the state budget, namely the sovereignty of the people. This has led to the loss of budgetary rights held by the House of Representatives. Based on this criticism, this study tries to find other perspectives and approaches in reading the formulation of popular sovereignty over the state budget by asking two questions; First, whether the amendments to the 1945 Constitution have degraded the existence of the state budget from a philosophical point of view; Second, how is the formulation of popular sovereignty over the state budget in the post-amendment 1945 Constitution? The research concluded that the philosophy of the state budget after the amendment of the 1945 Constitution is the sovereignty of the people. The sovereignty of the people over the state budget is formulated in several articles, which can be divided into formulations in formal aspects and formulations in material aspects. Abstrak Penelitian ini bertolak dari berbagai kritik atas hasil perubahan Pasal 23 UUD NRI 1945, yang pada dasarnya memandang bahwa hasil perubahan telah mendegradasi filosofi anggaran negara, yaitu kedaulatan rakyat. Hal ini membawa konsekuensi pada hilangnya hak anggaran yang dimiliki oleh Dewan Perwakilan Rakyat. Atas kritik tersebut, penelitian ini mencoba mencari sudut pandang dan pendekatan lain dalam membaca formulasi kedaulatan rakyat atas anggaran negara dengan mengajukan dua pertanyaan; Pertama, apakah perubahan UUD 1945 telah mendegradasi keberadaan anggaran negara dari sudut filosofi?; Kedua, bagaimana formulasi kedaulatan rakyat atas anggaran negara dalam UUD 1945 pasca perubahan? Hasil penelitian menyimpulkan bahwa filosofi anggaran negara pasca perubahan UUD 1945 adalah kedaulatan rakyat. Kedaulatan rakyat atas anggaran negara tersebut diformulasikan dalam beberapa pasal, yang dapat dibedakan menjadi formulasi dalam aspek formil dan formulasi dalam aspek materil.